Mothers’ Perceptions of System-Related Burden Following Their Youth’s Psychiatric Hospitalization: A Longitudinal Qualitative Study - Katherine M. Harris; Debora G. Goldberg; David B. Goldston; MacKenzie C. Feeken; Abigail B. Fry; Lauren Seibel; John F. Curry; Stephanie S. Daniel; Otima Doyle; Bridget E. Weller; Christianne L. Esposito-Smythers (Administration and Policy in Mental Health and Mental Health Services Research, 2026)
Abstract The period following youth psychiatric hospitalization is characterized by considerable caregiver burden. Through research suggests that mental health system involvement, socioeconomic status, and change over time may influence caregiver experiences, these areas remain underexplored. Using qualitative methods, this study examined aspects of the mental health system that contribute to parental burden in the year following youth psychiatric hospitalization and compared burden between mothers with high and low household incomes. Drawing from a longitudinal dataset of 252 mothers with an adolescent recently discharged from psychiatric hospitalization, we randomly selected 20 mothers with high (>$100,000) and low (